Die böhmischen Länder in den Wiener Zeitschriften und Almanachen des Vormärz (1805-1848) Tschechische nationale Wiedergeburt - Kultur- und Landeskunde von Böhmen, Mähren und Schlesien - Kulturelle Beziehungen zu Wien. Teil IV: RELIGION - RECHT - LANDESKUNDE - POLITISCHE ÖKONOMIE - NATURWISSENSCHAFTEN UND MATHEMATIK - Marinelli-König, Gertraud (Verlag der Österreichischen Akademie der Wissenschaften, 2016)
The present volume contains a critical suvey of entries collected from periodicals - learned journals and entertaining weeklies which were published in Vienna during the 1st half of the 19th century concerning the field of investigation which is the historical region of present day Czech Republic back then part of the Habsburg Empire with Vienna as the capital. The material collected in the present volume does cover the fields "Religion", "Law", "Area studies", "Political economy", "Natural sciences and mathematics" thus completing the study with three parts already in print: part I (2011) "Literature and literary history"; part II (2013) "Linguistics", "Philosophy, esthetics, rethorics","Historiography", "Education"; part III (2014) "The Arts". An index will be available online once the book is released, a general index in a print version will be provided in time.